Peganutonin A: computationally informed synthesis of its revised structure - Saranya, N. Sathya Sai; Choudhury, Rahul; Supekar, Prathmesh R.; Beduru, Srinivas; Williams, Craig M.; Elyashberg, Mikhail E.; Kutateladze, Andrei G.; Bates, Roderick W.; Reddy, D. Srinivasa (Journal of Natural Products, 2025)
The structure of the recently isolated natural product peganutonin A was shown to be incorrect by analysis of the reported spectroscopic data, and therefore, the structure was reassigned utilizing computational methods. Subsequently, the computationally proposed reassignment was confirmed by total synthesis, which was achieved in seven steps from 6-methoxyindole. It is assumed that peganutonin A is not a natural product but an artifact arising from photooxidation of the alkaloid harmaline.

Ready access to benzodiazocines from tryptamines: a druggable scaffold toward antiviral agents - Saranya, N. Sathya Sai; Choudhury, Rahul; Routholla, Ganesh; Supekar, Prathmesh R.; R, Nandhakumaar; Martin, Alna Kuriyickal; Muruganandham, Renuga Devi; Kumar, Bokara Kiran; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2025)
Herein we report the first synthesis of the proposed structure of a benzodiazocine natural product, peganutonin A. Considering the druggable nature of benzodiazocine and its limited exploration in the field of medicinal chemistry, we generalized the approach and created a library of compounds useful for various biological activities. Key steps in present approach include tryptamine cyclization facilitated by tert-butyl hypochlorite and cleavage of the fused indole ring using ozonolysis. Preliminary screening of the synthesized compounds resulted in potent antiviral compounds against the SARS-CoV-2 virus.
Keywords: Benzodiazocine; drug discovery; Indole cleavage; Lipinski's rule of Five; SARS-CoV-2 inhibition; Tryptamine